Performance enhancement of transmission system using double-pass EDFA with built-in Variable Optical Bragg Grating - Jamaludin M.Z.; Abdullah F.; Rahman F.A.; Mahdi M.A.; Abdullah M.K. (2023)
In this paper we demonstrate experimental results of a double-pass erbium-doped fiber amplifier with built-in Variable Optical Bragg Grating (DPF-EDFA) to enhance the performance of the transmission system. The system has achieved power gain of 6 dB which can be translated into an improvement to the distance of about 24 km compared to the conventional double-pass EDFA (DP-EDFA). 2007 IEEE.